Orthodontics principles and practice - Gill, Daljit S.; Naini, Farhad B. (Dental update (Wiley-Blackwell), 2011)
"Orthodontics: Principles and Practice is the latest in the Dental Update books series, offering a clear and comprehensive guide to contemporary orthodontic practice. Offering a highly practical clinical manual format, it covers patient assessment, diagnosis and treatment planning of both standard class malocclusions and specific entities (such as impacted teeth, digit sucking habits and asymmetries) appliance techniques, complex and multidisciplinary care, and retention"--Provided by publisher.